Campaign on awareness of the negative impacts of cyberbullying [Kampanye kesadaran tentang dampak negatif dari cyberbullying] - Elizar, Elizar; Zulkifley, Mohammad Asyraf; Muharar, Rusdha (Buletin Pengabdian, 2024)
Cyberbullying has evolved into a significant issue that frequently affects teenagers in today's society. This can be attributed to the fact that teenagers spenda significant amount of time on the internet, particularly on social media platforms. It is vital to take preventative measures against cyberbullying because these activities can have a significant influence on the mental health of teenagers. Awareness campaigns about the negative impacts of cyberbullying are one of the prevention measures through socialization to high school students regarding the dangers of cyberbullying actions. We hope that by participating in these activities, students will become more conscious of the need to take preventative measures against cyberbullying in the future.